KEPUTUSAN PEMBELIAN DITINJAU DARI CITRA MEREK, KERAGAMAN PRODUK DAN KUALITAS PELAYANAN (STUDI KASUS PADA KONSUMEN MINISO SOLO GRAND MALL SURAKARTA) - Maya Evelina Putri Prisnata; Sarsono Sarsono; Siti Maryam (ITB AAS Indonesia Surakarta, 2023)
The goal of the research is to identify and assess the impact of brand image, product diversity, and service quality on purchase decisions (a case study of Miniso Solo Grand Mall Surakarta customers). This study will take place in Miniso Solo Grand Mall Surakarta. This study employs quantitative methods. This study took four months to complete. The participants in this study were all Miniso Solo Grand Mall Surakarta customers. The sample size for this study was 100 people. In place of non-probability sampling, deliberate sampling was used in this investigation. The findings revealed that brand image, product diversity, and service quality all had a favorable and important impact on purchasing decisions at Miniso Solo Grand Mall Surakarta. in the model of 51.6%, while the remaining variables of 48.4% are impacted by additional elements which were ignored in this investigation. Keywords : Brand Image, Product Diversity, Service Quality, Purchase Decision